Disease Response Assessment Modalities in Chronic Myeloid Leukemia: Past, Present, and Future - Mishra, Deepak Kumar; Dey, Indranil; Demde, Rakesh; Vinarkar, Sushant; Parihar, Mayur (Indian Journal of Medical and Paediatric Oncology, 2023)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm caused by the BCR::ABL1 fusion gene, which results from a reciprocal translocation between chromosome 9 and 22 t(9;22)(q34;q11). The use of tyrosine kinase inhibitor (TKI) against the chimeric BCR::ABL1 fusion protein has led to a paradigm shift in CML patient outcomes. Despite generational advancements in TKI, a fraction of patients harbor residual disease or exhibit resistance to TKI. The importance of disease monitoring and detection of resistance mechanisms has gained prominence with increasing knowledge about disease evolution. In the past, cytogenetic techniques such as karyotyping and fluorescence in situ hybridization were widely utilized for monitoring disease and prognostication. These techniques had various challenges related to limited sensitivity in minimal residual disease (MRD) monitoring; however, their importance still holds in the detection of additional chromosomal aberrations and in cases with cryptic insertions, variants, and masked Philadelphia chromosome. Molecular genetics has evolved significantly from the past to the present times for MRD monitoring in CML patients. Qualitative reverse transcription polymerase chain reaction (RQ-PCR) can be performed at diagnosis to detect the BCR::ABL1 transcript, while quantitative RQ-PCR is the most widely used and well-standardized MRD monitoring method. The DNA-based assays demonstrated high sensitivity and specificity, with many efforts directed toward making the laborious step of BCR::ABL1 breakpoint characterization less tedious to increase the utility of DNA-based MRD approach in the future. Flow cytometric–based approaches for the detection of the BCR::ABL1 fusion protein have been under trial with a scope of becoming a more robust and convenient methodology for monitoring in the future. Upcoming techniques such as digital PCR and ultra-deep sequencing next-generation sequencing (UDS-NGS) have shown promising results in residual disease monitoring and detection of resistance mutations. Novel MRD monitoring systems that are independent of BCR::ABL1 fusion such as the detection of CD26+ leukemic stem cells and microRNA mutations are the future of residual disease monitoring, which can go up to the level of a single cell. In this review, we tried to discuss the evolution of most of the above-mentioned techniques encompassing the pros, cons, utility, and challenges for MRD monitoring and detection of TKI resistance mutations.
Keywords: hematology; medical oncology; pathology